Numerical simulation of simulate an anomalous solute transport model via local meshless method - Ahmad, Imtiaz; Khan, Muhammad N.; İnç, Mustafa; Ahmad, Hijaz; Nisar, K. S. (Elsevier, 2020)
In this article, an efficient local meshless technique is implemented for the numerical solution of an anomalous mobile-immobile solute transport process. The process is mathematically modeled as a time fractional mobile-immobile diffusion equation in sense of Caputo derivative. An implicit time integration procedure is used to semi-discretize the model in the time direction whereas the space derivatives of the model is discretized by the proposed meshless technique based on inverse multquadric radial basis function. The demand of meshless techniques increment because of its meshless nature and simplicity of usage in higher dimensions. This technique approximate the solution on set of uniform and scattered nodes and it leads to a sparse and well-conditioned coefficient matrices. Numerical examinations on some test problems are performed to exhibit suc-cessful applications and accuracy of the local meshless technique on regular and irregular compu-tational domains. (C) 2020 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Meshless method; Radial basis function; Caputo derivative; Mobile-immobile solute transport model; Irregular domain